The Influence of Budget Participation and Budget Target Clarity on Managerial Performance at the Bale Bandung District Court - Butar, Yenny Imelda Butar; Silviana , Silviana (Publikasi Indonesia, 2025)
This study aims to analyze the influence of work-life balance and physical work environment on the performance of Civil Servant Teachers (ASN) at SMP Negeri 7 Cimahi. A quantitative approach was employed, using survey methods and data collection techniques such as questionnaires, interviews, observations, and documentation. The sample included 36 ASN teachers as respondents for the independent variables and the principal for the dependent variable. The findings revealed that work-life balance was categorized as balanced, with the highest score in the sub-variable of involvement balance (4.24). The physical work environment was rated as good, with workplace safety being the most prominent sub-variable (4.15). Teacher performance was generally categorized as good, with social competence achieving the highest score (4.31). Multiple linear regression analysis revealed that work-life balance and physical work environment positively and significantly influenced teacher performance, both partially and simultaneously, with a simultaneous influence rate of 60.1%. This study contributes to policy development aimed at enhancing work-life balance and optimizing the physical work environment to support teacher performance and improve education quality.